How to Conduct High-Quality Systematic Review and Meta-analysis in Radiology and Interventional Radiology - Manish Shaw; Sanjiv Sharma (Indian Journal of Radiology and Imaging, 2025)
Systematic reviews and meta-analyses form a secondary research methodology that identifies and critically appraises all the relevant studies that are available in various databases to answer a particular research question in an unbiased and systematic manner. In the pyramid of level of evidence, the systematic review of high-quality studies is placed at the highest hierarchy position. Meta-analysis is the statistical analysis of the systematic review that provides pooled estimates of the effect of individual studies in the systematic review, but sometimes a meta-analysis may not always be possible. This article elaborates the key steps to conduct a high-quality systematic review and meta-analysis in the field of radiology and intervention radiology, which will help the readers to design and conduct them along with to understand and interpret this secondary research.